Speech Features in Food Endorsement of Indonesian Influencers: a Study of Language and Gender - Assayyidah Bil Ichromatil Ilmi; Sailal Arimi (SUAR BETANG, 2023)
This study aims to identify the speech features employed by male and female influencers while promoting food. This research decided to apply a qualitative method, specifically in the form of a case study. Meanwhile, the researchers chose observation through social media, namely Instagram, as the data collection process. The data analysis consists of three stages, such as reduction, presentation, and conclusion. The researchers found that the female influencers use speech features are intensifier, emphatic stress, tag question, rising intonation, empty adjectives, specialized, hypercorrect grammar, super polite forms, avoidance of strong swear, and one form that belongs to the men known as command and directive. Meanwhile, the speech features employed by the men are command and directive, swearing and taboo words, compliments, and theme, and three forms of speech feature that belong to women, which are intensifier, empty adjective, and emphatic stress. The finding of this study is that both genders are not constantly with their own speech features. Both genders also applied speech features that belong to the opposite gender while doing promotion, although the language features of each gender dominate the respective results. AbstrakPenelitian ini bertujuan mengidentifikasi fitur tuturan yang digunakan oleh influencer pria dan wanita saat melakukan promosi makanan. Penelitian ini menggunakan metode kualitatif, khususnya dalam bentuk studi kasus. Penulis memilih observasi melalui salah satu media sosial, yakni Instagram, pada proses pengumpulan data. Proses analisis data terdiri atas tiga tahap, yaitu reduksi, penyajian, dan penarikan simpulan. Penulis menemukan bahwa para influencer wanita menggunakan fitur ucapan yang intensif, penekanan tegas, tanda pertanyaan, intonasi tinggi, kata sifat kosong, kata khusus, tata bahasa yang berlebihan, bentuk sangat sopan, menghindari umpatan yang kuat, dan satu bentuk milik pria yang dikenal sebagai perintah dan direktif. Sementara itu, ciri-ciri tuturan yang digunakan oleh influencer laki-laki adalah tuturan perintah dan direktif, umpatan dan kata-kata tabu, pujian, dan tema, serta tiga bentuk tuturan yang dimiliki wanita, yaitu intensifier, kata sifat kosong, dan tekanan empatik. Temuan dari penelitian ini adalah bahwa kedua jenis influencer tidak selalu memiliki fitur bicara mereka sendiri. Mereka juga menerapkan fitur bicara milik lawan jenis saat melakukan promosi meskipun hasilnya didominasi oleh ciri fitur bahasa pada masing-masing gender.